2. Distance Education Prompted by Covid-19 Lockdowns: A Challenge for Teaching Musical Performing Arts - Marisi Rossella (Sciendo, 2022)
In 2020 and 2021, Information and Communication Technology (ICT) played a crucial role during the lockdowns, giving people the chance to continue doing business, entertainment, and education. In the education sector, in response to the outbreak of COVID-19, many countries adopted ICT-enabled distance education, which shows both positive and problematic features. The most concerning aspects relate to the digital divide, the readers' ability to assess the trustworthiness of texts found on the Web, the educators' competence in using ICT by incorporating it in their pedagogical practice, and the applicability of distance education to the teaching of performing arts.